Numerical study on off-current features in an organic transistor by controlling electrode-overlap area. (12th August 2016) - Song, Dong-Seok; Kim, Hyeok; Vincent, Premkumar; Hahn, Joonku; Park, Jaehoon; Bae, Jin-Hyuk
ABSTRACT: We investigate the effect of the source/drain-to-gate electrode overlap area on the off-current features in organic thin-film transistors (OTFTs). For the numerical simulation, we used 2-D Atlas, a device simulator based on a two-dimensional Technology Computer Aided Design (TCAD) software tool provided by Silvaco. Both channel and overlap lengths are varied from 1 μm to 1000 μm. The off-current decreases with increasing channel length, whereas variations in the overlap area show a negligible effect on both on- and off-state currents.